H01 How Do Mental State Inferences Shape The Social World In Huntington's Disease?. (17th September 2014) - Eddy, CM; Rickards, H
Abstract : Background: Previous research has indicated that Huntington's disease (HD) can be associated with deficits in Theory of Mind (ToM): the ability to understand mental states such as beliefs and emotions. Aims: We explored the tendency of patients with HD to attribute mental states to ambiguous stimuli in the form of a series of video-clips involving animated shapes. Some of these animations are considered to involve random movements of two triangles, while others are commonly interpreted as depicting simple or more complex social interactions prompting the inference of mental states to the shapes (e.g. chasing, persuading). Methods: Forty patients with genetically determined HD and twenty healthy controls matched for age and gender participated in the study. In addition to the video animations task we administered measures of alexithymia, mood disorder, executive functions and motor symptoms. Results: HD gene carriers showed significant evidence of alexithymia in comparison to controls. Moreover, individuals with HD exhibited a deficit in the attribution of intentions on the animations task. In patients with motor onset, aspects of performance on the animations task were correlated with motor symptom severity and alexithymia. However, subgroup analyses revealed a significantly reduced tendency to infer intentions was apparent in patients without motor symptoms and intact executive functions. Conclusions: HD is associated with a deficit in the spontaneous attribution of mental states, and therefore a reduced propensity to adopt the intentional stance. Our findings further suggest that subtle changes in ToM can be detected prior to motor onset in HD.